A Bibliometric Analysis of Strategic Flexibility and Performance - Ayundha Evanthi; Ratih Mukti Azhar (Future Science, 2022)
The objectives of this research are: (1) to examine strategic flexibility and performance by emphasizing their relationships, dimensions, and roles of context (2) to identify the relationship between strategic flexibility and performance that can be used for future theory development. This research uses bibliometric analysis to map how strategic flexibility is intended from several previous journals using VOSviewer.